IMPLEMENTASI PERATURAN DAERAH KABUPATEN PANDEGLANG NOMOR 12 TAHUN 2010 TENTANG PEDOMAN PENYELENGGARAAN WARALABA (Studi Kasus di Pasar Pandeglang) - Gian Sumarna Gian Sumarna (NIAGARA Scientific Journal, 2016)
Implementation of Pandeglang Regency Regional Regulation No. 12 of 2010 concerning "Franchise Implementation Guidelines" in Pandeglang Market is still not effective.The main problem in this research is: what is the implementation process of Pandeglang Regency Regional Regulation No. 12 of 2010 concerning Guidelines for Implementing Franchises in the Form of Modern Stores (Alfamart and Indomaret) case studies at Pandeglang Market?The research method used was descriptive method. This research was conducted at Pandeglang Market. Meanwhile, the informants consisted of Members and Secretariat of DPRD Pandeglang Regency, Head of Sub-division and Legislative Executors Legal Section of Pandeglang Regional Secretariat, Head of Administrative Unit of Integrated Licensing Service Agency Kab. Pandeglang, Head of Trade, Company Registration and Promotion Section, and Subdivision. Evaluation Planning and Reporting DISPERINDAGPAS Kab. Pandeglang, Head of UPT Pasar Pandeglang, Head of Pandeglang Market, Civil Servant Investigator SATPOLPP Kab. Pandeglang, Head of District Spatial Planning Division. Pandeglang, Indomaret and Alfamart Management, Indomaret and Alfamart Pandeglang Market Franchisees, Pandeglang Market Rhino Cooperative, and Pandeglang Market Traditional Traders. The results of the study concluded that the implementation of Pandeglang Regency Regional Regulation Number 12 of 2010 concerning Guidelines for Franchise Organizations in the Form of Modern Stores (Alfamart and Indomaret) case studies at Pandeglang Market have not been effective, this can be seen from various aspects: Policy Size and Objectives, Resources in implementing the guidelines for the implementation of franchising in Pandeglang Regency, Characteristics of Implementing Agents, Implementing Attitudes/Trends as well as Inter-Organizational Communication and Executing Activities.